Peningkatan Kemampuan Menulis Surat Lamaran Pekerjaan Melalui Model Pemelajaran Berbasis Pengalaman Pada Siswa Kelas XII SMK Swasta As-Syifa Kisaran - Rusda Nita Nelly Manurung (Medan Resource Center, 2022)
The purpose of this study was to describe an increase in the ability to write job application letters through an experience-based learning model for Class XII students of As-Syifah Kisaran Private Vocational School. This type of research is classroom action research (PTK). The subjects in this study amounted to 30 students which were carried out in 2 cycles. Data collection techniques consist of observation and tests. The procedures used are (1) planning stage, (2) implementation, (3) observation, (4) reflection. The results of this study indicate that it can increase learning activities. this can be seen from the teacher's activities in the first cycle obtained an average of 26.4 with